The Effect of Organisation Brand to Employee Engagement through Compensation and Benefit in Startup Business - Astri Utami Indriyani (Universitas Airlangga, 2017)
The startup business in Indonesia has become a popular way recently. Especially for them who wants to begin their business empire. The business that run by the employee. Employee needs to bring with them the brand of the business because they have to feel the brand as their own identity. Some research find that the more engage the employee, the more productive they become. On the other side, compensation and benefit are also the factor to determine the engagement of the employee. This paper would like to tests the hypothesis that organisation brand is having some effect on employee engagement. The evidence collected from 30 employee on various startup business. The result shows that organisation brand have the effect on employee engagement, as well as the benefit but not with the compensation.